Critical Analysis of The Interplay Between Nursing and Optical Sciences - Alotaibi, Majed Mhaya; ALSHEHRI, ADIL SAEED; Al Muammar, Hussein Saleh; Hazazi, Yousef Mohammed; Shajiri, Mohammed Mohatlem; Muhajeb, Majed Naser Ali; mashyakhi, adel dhufuallah; Murayr, Abdulleh Ahmed Hamd; Jened, Ahod Maber Abdu; Hajaji, Zahra Ahmed (Journal of Ecohumanism, 2024)
The combination of nursing and optical science is a relatively new field that is not well-researched. With the shift in population age and the importance of the whole-person approach to health, the role of ophthalmic care for patients’ general health is gradually becoming more noticeable. This paper aims to critically discuss the relations between nursing and optical sciences concerning the influence of optical health on the effects on nursing and patients and to define the possibilities of increasing the efficiency of nursing practice concerning the opportunities for optical sciences integration. This paper presents a literature review of the current knowledge in the field, along with the problems and challenges that can be analyzed, and develops an action plan for further research studies and practice advancements. Thus, this paper aims to advance the current understanding of interdisciplinary practice in healthcare and its relevance to enhanced patient care.